Sanitasi Lingkungan dan Pengelolaan Sampah pada Kejadian Stunting - Metriana, Metriana; R. Azizah, R. Azizah; Sulistyorini, Lilis; Yunara, Yulia (Journal of Telenursing (JOTING), 2024)
The aim of this study is to analyze the relationship of environmental sanitation and its impact on children's health and growth. The Systematic Review with Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) was used as a guideline. The results of this study are: (1) Environmental sanitation in terms of the use of clean water has a correlation with stunting; (2) Environment sanitation from the aspect of waste management has a correlation with stunting; and (3) Environment sanitation from the aspect of toilet facilities has a correlation with stunting. Poor sanitation will increase the incidence of infectious diseases which have an impact on energy intake in the body, so that nutrients are difficult to absorb by the body so that growth is stunted or disrupted which is called stunting. Keywords: Clean Water, Environmental Sanitation, Stunting, Waste Management